Effect of inclusion of NDF in ration of Bergamasca ewes in lactation about the milk production and composition - Natel, Andressa Santanna [UNESP]; Siqueira, Edson Ramos de [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Martins, Marcela Buosi [UNESP]; Almeida, Marco Túlio Costa [UNESP]; Fernandes, S. [UNESP] (International Organization of Scientific Research, 2013)
Ruminant milk composition is directly affected by diet, which can interfere in rumen fermentation and in the availability of precursors for the synthesis of fat, protein and lactose. This study evaluated the effect of the inclusion of neutral detergent fiber (NDF) on dry matter intake, feed efficiency, milk production and composition of Bergamácia ewes. Sixteen lactating ewes were divided into four 4x4 Latin squares. The experimental diets consisted of protein concentrate and alfalfa hay. Concentrate:forage ratios varied according to treatment, to achieve the required levels of NDF: (T1) 23%, (T2) 32%, (T3) 41% and (T4) 50% NDF in total ration. The ewes were milked twice a day in a milking machine. Milk samples were collected for two days in each sub-period to determinate the composition by infrared method. There was a linear effect (P<0.01) in milk production and average daily production efficiency (P<0.02) with the inclusion of fiber in the diet. A quadratic effect was observed for DMI (1.69, 1.71, 1.58 and 1.32 kilograms). Increasing fiber in the diet reduced milk production without altering its composition. The maximum intake was achieved at 37.8% NDF in the ration.
Keywords: Dry matter intake; Lactation; Neutral detergent fibre; Efficiency